PENINGKATAN PEMAHAMAN MAHASISWA TERHADAP IMPLEMENTASI MANAJEMEN DAN PENGEMBANGAN PROGRAM BIMBINGAN DAN KONSELING DI SMP MELALUI FOCUS GROUP DISCUSSION - Riza Hidayati; Maharani; Nurlaila Syipa’unnupus; Indah Shofianita; Latif Hamidi; Eli Ermayanti; Luk Luil Adni; Sintia Pratiwi; Siti Zawyah Nanga Wara; Rizkia Maulida; Anisa Sapira; Silmi Rostiana; Imam Nawawi Zain; M. Muzayyin Fanani; Fitri Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the improvement of university students' understanding of the implementation of guidance and counseling (GC) management and program development at junior high schools through the Focus Group Discussion (FGD) method. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The findings indicate that prior to participating in the FGD, students' understanding of the implementation of GC management and program development was limited to conceptual knowledge and they had difficulty relating theory to actual school practices. After participating in the FGD, students demonstrated a significant improvement in understanding, particularly regarding the stages of GC program management, including needs assessment, planning, implementation, evaluation, and program follow-up. This improvement was supported by interactive discussions, the facilitator's expertise, the relevance of the materials to real school practices, and opportunities for participants to exchange ideas and experiences. However, several challenges were identified, including differences in students' prior knowledge, limited field experience, and the relatively short duration of the FGD sessions. Therefore, the study concludes that Focus Group Discussion is an effective learning strategy for bridging the gap between theory and practice and for enhancing the professional readiness of Guidance and Counseling students in implementing and developing school guidance and counseling programs.